Evaluating the nutrient and fatty acid profiles of black soldier fly larvae (Hermetia illucens) raised on various diets in Thailand - Pittarate, Sarayut; Arjin, Chaiwat; Vivekanandhan, Perumal; Swathy, Kannan; Chiu, Chun-I; Mekchay, Supamit; Hnokaew, Patipan; Sartsook, Apinya; Siripan, Thanandon; Sringarm, Korawan; Krutmuang, Patcharin (Frontiers in Insect Science, 2026)
IntroductionBlack soldier fly larvae (BSFL) have gained increasing attention as a sustainable alternative protein source for animal feed, particularly when reared on organic by-products. This study evaluated the nutritional composition of BSFL reared on different organic substrates to support sustainable feed production.MethodsBSFL were reared on five organic substrates: chicken feed, pig feed, soy milk residue, coconut press cake, and perilla cake. Larvae were cultivated in metal trays (23 × 15 cm) for 2–4 weeks under controlled conditions (28 ± 2 °C; 65 ± 5% relative humidity). At the prepupal stage, larvae were harvested and analyzed for dry matter, crude protein, crude fiber, ether extract, ash, growth performance, and fatty acid profiles.ResultsSignificant differences in nutritional composition were observed among substrates. Crude protein content was high in larvae fed chicken feed (50.55 ± 0.07%), pig feed (52.10 ± 0.14%), soy milk residue (52.15 ± 0.78%), and perilla cake (47.20 ± 0.00%). Crude fiber was highest in larvae fed soy milk residue (7.19 ± 1.48%) and perilla cake (5.38 ± 0.25%). Fatty acid analysis revealed substantial levels of saturated and unsaturated fatty acids, including palmitic, oleic, and linoleic acids. Larvae reared on coconut press cake showed the highest saturated fatty acid content (74.91 ± 0.03%), while those fed soy milk residue exhibited the highest oleic (26.68 ± 0.06%) and linoleic acid (38.44 ± 0.07%) contents, resulting in increased polyunsaturated fatty acids (38.57 ± 0.03%).DiscussionThe findings demonstrate that organic by-products commonly available in Thailand are suitable substrates for BSFL production and significantly influence larval nutritional quality. These substrates enable the production of nutrient-rich, cost-effective, and sustainable insect-based feed, contributing to responsible consumption, waste valorization, and food security.